2020
DOI: 10.4209/aaqr.2020.06.0275
|View full text |Cite
|
Sign up to set email alerts
|

Addressing COVID-19 Spread: Development of Reliable Testing System for Mask Reuse

Abstract: While the novel coronavirus pandemic (COVID-19) continues to wreak havoc globally, self-protection from possible infection by wearing a mask in daily life has become the norm in many places. The unprecedented demand for masks has now attracted attention on their filtration efficiency. Furthermore, the widespread use of disposable masks has led to shortage of filter materials and problems with their haphazard disposal. In this study, a testing system that is based on standardized methods has been established an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…[ 19 ] Using the same size latex spheres, Lu et al's surgical mask produced average PFE results of 80.2%. [ 20 ] In comparison, our L2 masks performed at a PFE of 94.2 ± 0.6%, and the L3 masks performed at a PFE of 94.9 ± 0.3%. While these PFEs exceed many of those in the literature, we must note that there is little reference to the certification level in the previous studies, whereas our surgical masks were certified at Level 2 and Level 3.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…[ 19 ] Using the same size latex spheres, Lu et al's surgical mask produced average PFE results of 80.2%. [ 20 ] In comparison, our L2 masks performed at a PFE of 94.2 ± 0.6%, and the L3 masks performed at a PFE of 94.9 ± 0.3%. While these PFEs exceed many of those in the literature, we must note that there is little reference to the certification level in the previous studies, whereas our surgical masks were certified at Level 2 and Level 3.…”
Section: Resultsmentioning
confidence: 92%
“…For example, Bagheri et al (2021), Shakya et al (2016), and Lu et al (2020) constructed apparatuses that generate a polystyrene latex aerosol which was diluted and sent to the material sample, where particle concentration measurements were performed using various particle analyzers or scanning mobility particle sizers. [ 18 , 19 , 20 ] Whereas Lu et al utilized a charge neutralizer downstream of their aerosol generator, the authors of the other two studies did not. Air flow rates at the sample also varied slightly—but within the constraints of the F2299 standard—from ≈7.3 to 19 L min –1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, with two layers of woven fabrics, the PFE ranged from 12.6 % for woven cotton to 30.5 % for flannel, outlining the ineffectiveness of clothbased face coverings against sub-micron aerosols. 37,38 Thus, it is desirable to include a more effective filtration material in layers, particularly for use in the moderate to heavy flow regime expected under moderate physical exertion. 43…”
Section: Aerosol Filtration Efficiency Of Single Layer Materialsmentioning
confidence: 99%
“…32,36 Several works have shown that cloth-only layers do not provide adequate blocking of submicron aerosols. 37,38 Accordingly, the WHO and other public health agencies are recommending a 3-layer combination comprising a middle non-woven material. To this extent, some studies examined vacuum bag 32 and furnace filters, such as HEPA and MERV-13.…”
Section: Introductionmentioning
confidence: 99%